2016
DOI: 10.1186/s12882-016-0370-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of patients with severe hyponatraemia is related not only to hyponatraemia but also to comorbidities and to medical management: results of an observational retrospective study

Abstract: BackgroundThe true cause of death in severe hyponatraemic patients remains controversial. The present study aimed to analyse the relationship between comorbidity, medical management and prognosis in severe hyponatraemic patients.MethodsMedical records of all patients hospitalised in our institution in 2012 with a plasma sodium ≤120 mmol/l were retrospectively analysed.ResultsOne hundred forty-seven of 64 723 adult patients (0.2 %) were identified with severe hyponatraemia. In-hospital mortality rate was 24.5 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
(51 reference statements)
2
9
1
1
Order By: Relevance
“…Moreover, the participants who got DAMA due to worsening clinical status could be the reason for the underestimation of the in-hospital mortality. The severity of hyponatremia was not found to be associated with mortality or poor outcome in our study which is similar to the findings in many other recent studies [25][26][27] (Table 4). In the subgroup analysis, patients with delirium had a poor outcome which was tending to achieve significance empha-sising the fact that delirium is associated with high mortality 28 .…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the participants who got DAMA due to worsening clinical status could be the reason for the underestimation of the in-hospital mortality. The severity of hyponatremia was not found to be associated with mortality or poor outcome in our study which is similar to the findings in many other recent studies [25][26][27] (Table 4). In the subgroup analysis, patients with delirium had a poor outcome which was tending to achieve significance empha-sising the fact that delirium is associated with high mortality 28 .…”
Section: Discussionsupporting
confidence: 93%
“…They found that both underlying comorbidities assessed by the Charlson Comorbidity Index, and low serum sodium levels on admission predicted 1‐year mortality, suggesting that the correlation of serum sodium and mortality emphasizes both serum sodium itself and the underlying disease . Similar to this, some recent studies suggest that the mortality in patients with hyponatremia appears mainly driven by comorbidities, but hyponatremia could have a detrimental effect by itself . Barsony et al .…”
Section: Discussionmentioning
confidence: 77%
“…Correction rates are affected by the underlying cause (30,31). Hyponatremia due to heart failure, cirrhosis, kidney injury, or malignancy does not spontaneously resolve and may not be treated; patients with these disorders often die in the hospital.…”
Section: How Much Correction Is Enough?mentioning
confidence: 99%
“…Lower serum sodium concentrations are associated with more rapid correction rates (30)(31)(32). Paradoxically, the lowest serum sodium levels are associated with the lowest mortality; hospitalized patients with very low serum sodium levels are more likely to have been admitted for medication-induced hyponatremia, and patients with milder hyponatremia are more likely to have been hospitalized for severe, potentially fatal illness (28,30,31).…”
Section: How Much Correction Is Enough?mentioning
confidence: 99%